2022
DOI: 10.1021/jacs.2c03649
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Diazocine-Based Estrogen Receptor Agonists: Stabilization of the Active Form inside the Receptor

Abstract: Photopharmacology is an emerging approach in drug design and pharmacological therapy. Light is used to switch a pharmacophore between a biologically inactive and an active isomer with high spatiotemporal resolution at the site of illness, thus potentially avoiding side effects in neighboring healthy tissue. The most frequently used strategy to design a photoswitchable drug is to replace a suitable functional group in a known bioactive molecule with azobenzene. Our strategy is different in that the photoswitch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 89 publications
0
18
0
3
Order By: Relevance
“…[13][14][15] Early spectroscopic experiments reported that many azo dyes undergo a transcis photoisomerization 1,[13][14][15][16][17] upon excitation with blue or UV light, which can be exploited for photoswitching applications. [18][19][20][21][22] Subsequent studies present detailed investigations shedding light on the mechanism of photoisomerization in azo dyes. [23][24][25][26][27][28][29][30] It is generally accepted that when azobenzene is illuminated, the decay of the initial photoexcited state occurs through a torsional rotation of the +CNNC dihedral resulting in population of the higher energy cis-isomer.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Early spectroscopic experiments reported that many azo dyes undergo a transcis photoisomerization 1,[13][14][15][16][17] upon excitation with blue or UV light, which can be exploited for photoswitching applications. [18][19][20][21][22] Subsequent studies present detailed investigations shedding light on the mechanism of photoisomerization in azo dyes. [23][24][25][26][27][28][29][30] It is generally accepted that when azobenzene is illuminated, the decay of the initial photoexcited state occurs through a torsional rotation of the +CNNC dihedral resulting in population of the higher energy cis-isomer.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of photoswitchable molecules to address two distinct isomers of the same molecule by the non-invasive stimulus "light" opens numerous areas of potential application, including, but not limited to, chemical sensing, 1,2 smart materials, [3][4][5] data storage, 6 logic gates, 7 photopharmacology, [8][9][10][11] and life-like motion. 12 With the broad scope of potential applications arises the need for a wide variety of chemically stable photoswitches with distinct propertiessuch as excitation wavelength, the photostationary state (PSS) under irradiation and under ambient conditions, and thermal half-life τ1 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] These cyclic azobenzenes represent a small but fast-growing class of molecular switches. The eight-membered ring diazocines, whose photochemical properties have been investigated as early as 2009, 25 have recently been successfully applied in photopharmacology 10,11 and smart materials. 28 Comparison of the ethylene-bridged diazocine 25 with the oxamethylene-bridged diazocine 26 shows increased thermal half-life and photoconversion for the ethylene-bridged analogue.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Photopharmacology enables the optical control of biological processes with high spatiotemporal precision by using photoswitchable molecules that exhibit different activity in their different configurations. [11][12][13][14] This concept has been established for several protein classes, including nuclear receptors, [15][16][17][18][19][20] and is also appealing for LXR activation as it may reduce systemic side effects through local activation. [21] Especially for an application in cancer treatment, this approach holds potential by spatially limiting pharmacological effects to an intended site of action.…”
Section: Introductionmentioning
confidence: 99%